Impact of operating conditions on the removal of endocrine disrupting chemicals by membrane photocatalytic reactor - López Fernández, Raquel (Environmental technology, 2014)
This study focuses on the performance of a submerged membrane photocatalytic reactor for the removal of 17beta-oestradiol (E2) in the presence of humic acid (HA). In addition to the impact of operating parameters, such as membrane pore size, ultraviolet (UV) intensity and hydraulic retention time (HRT), the influence of long-term operation was also assessed by advanced characterization of the fouling layer formed on the membrane. The tighter (0.04 microm) hollow fibre polyvinylydene fluoride (PVDF) membrane was found to exhibit not only higher HA removal than the (0.2 microm) module (85% and 75%, respectively), but also greater transmembrane pressure (TMP) values and higher irreversible fouling. Long-term operation conditions have been simulated by conducting an ageing catalyst process and demonstrated a decrease in performance obtained with time. The artificially aged TiO2 resulted in higher TMP values and lower HA removals (about 10-20% decrease) compared with the non-aged catalyst. For E2 removal in the presence of HA, the passive adsorption of the oestrogen onto the organic matter was found to be significant (40% of the E2 adsorbed after I h), demonstrating the importance of the nature of the water matrix for this type of treatment process. An increase in the UV light intensity was observed to favour the E2 elimination, leading to more than 90% removal when using 64 W combined with PVDF membrane and an HRT of 3 h